RESPON TANAMAN JAGUNG MANIS (Zea Mays L.) TERHADAP PEMBERIAN PUPUK GUANO KELELAWAR DAN PUPUK GUANO WALET - SELVY ISNAENI; SITI NURHIDAYAH (Jurnal Agroteknologi, 2020)
Organic farming has become very important for the continuity of agriculture in Indonesia. In addition to harvesting organic crops is healthy, the process of organic cultivation is also an effort of farmers to make improvementets to soil quality. This research aim to determine how the response to the administration of various doses of bat guano fertilizer and guano swallow fertilizer on sweet corn plant by the addition of phosphate solvent microbes. The study was conducted in the experimental garden of the Faculty of Agriculture, Universitas Perjuangan Tasikmalaya. The experimental design used factorial randomized block design with 3 treatment of bat guano fertilizer dosage and 3 treatments of guano swallow fertilizer dosage, each treatment was repeated 3 times and each treatment was given phosphate solvent with the same dose. The result showed that there was an interaction between guano bat fertilizer and guano swallow at 6 and 8 week after planting leaves in the treatment of K0W1 (0 tons / ha bat guano + 2.5 ton / ha swallow guano) and K1W2 (2.5 tons / ha Bat guano + 3.75 tons / ha swallow guano), but there are no interaction on other parameters. There are no maximum doses for guano bats and guano swallow in the response of sweet corn plant.